PENDAMPINGAN BUDIDAYA SAYUR ORGANIK DENGAN SISTEM HIDROPONIK DI DESA BUMIAJI KOTA BATU - Hari Kurnia Safitri; Bambang Priyadi; Indrazno Siradjuddin; Mila Fauziyah (Publisher UPT P2M Politeknik Negeri Malang, 2021)
Bumiaji village is located on the slopes of the mountains with an altitude of 150mdpl. The majority of bumiaji villagers work as farmers. PKM in activities aim to help farmers in terms of increasing income and diverse agricultural produce on partner land. Currently the partner has about 800 m2 of land that is used for citrus cultivation. Because the old citrus harvest process is about 4-5 months, the partner needs additional income in addition to citrus cultivation. The training conducted by the PKM team is: (1) the introduction of hydroponic system knowledge; (2) training to grow vegetables with hydroponic system. By knowing and knowing the hydroponic system farmers / partners can develop hydroponic systems for various organic vegetables in the rest of the land, so that the results obtained are diverse and increase the income of partners.